2008
DOI: 10.1590/s1806-37132008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Padrões de sibilância respiratória do nascimento até o início da adolescência: coorte de Pelotas (RS) Brasil, 1993-2004

Abstract: Objective: To study the prevalence of wheezing patterns and their associations with independent variables. Methods: Cohort study of live births in 1993 in Pelotas, Brazil. A systematic subsample (20%) of the original cohort was evaluated at 6 months, 12 months and 4 years. At 10-12 years, 87.5% of the original cohort was contacted. Wheezing was categorized: transient, wheezing at 4 years but not at 10-12; persistent, wheezing at all evaluations; late-onset, wheezing at 10-12 years. Independent variables were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
2
8
0
5
Order By: Relevance
“…In a Brazilian cohort study, family history of asthma assessed at four years of age was significantly associated with the pattern of transient and persistent wheezing. 5 Other studies have found this association 16---18 , in agreement with the Asthma Predictive Index (API), which has parental history of asthma as a major criterion for the diagnosis of asthma in children with recurrent wheezing. 19 The presence of six or more episodes of upper respiratory tract infections in the first year of life, with early onset (before three months of age), was a factor associated with wheezing in this study (Tables 1 and 3).…”
Section: Discussionsupporting
confidence: 65%
“…In a Brazilian cohort study, family history of asthma assessed at four years of age was significantly associated with the pattern of transient and persistent wheezing. 5 Other studies have found this association 16---18 , in agreement with the Asthma Predictive Index (API), which has parental history of asthma as a major criterion for the diagnosis of asthma in children with recurrent wheezing. 19 The presence of six or more episodes of upper respiratory tract infections in the first year of life, with early onset (before three months of age), was a factor associated with wheezing in this study (Tables 1 and 3).…”
Section: Discussionsupporting
confidence: 65%
“…The reason for this gender difference is based on lower airway caliber male relative to the female gender 13 , this relationship, which is reversed as the child reaches adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Infants who have a family history of asthma 2,6,15 ,rhinitis 15 and allergic dermatitis have the greatest chance to present episodes of wheezing in the first 12 months of life, showing that heredity is an important risk factor for wheezing and asthma later 2,5,6,10,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a prevalência de sibilância e de diagnóstico médico de asma no presente estudo está situada entre os valores mais altos considerando os limites de variação descritos na literatura nacional 2,3,10,17,18 .…”
Section: Discussionunclassified
“…Esses fatores podem estar relacionados tanto à provável atopia quanto a infecções. Dentre as doenças presentes na infância, as principais são as infecções respiratórias e estas se configuram como fator de risco para asma 10,17,18 , com destaque para o papel das infecções virais, que podem causar sibilância em graus variados 19,20,21 . As mães podem superestimar a gravidade da doença do filho, no entanto, é pouco provável que diga que o mesmo está doente quando de fato não está.…”
Section: Discussionunclassified